Posterior-scleritis: Case report of an uncommon immune-related adverse event in the treatment of advanced endometrial cancer - Brandon I. Ing; Derek Kuhl; Deanna Glassman; Cynae A. Johnson; Shrina Patel; Amir A. Jazaeri (Elsevier, 2023)
As Immune checkpoint inhibitors are being expanded for use in gynecologic malignancies, rare immune-related adverse events are more frequently being reported. Here we describe a 63-year-old with Stage IIIB mismatch repair deficient uterine adenocarcinoma who underwent six cycles of carboplatin and paclitaxel with partial response but persistent disease. She was then started on single agent pembrolizumab. After six cycles of pembrolizumab, she developed bilateral vision changes and was diagnosed with posterior scleritis. Pembrolizumab was held and she was treated with oral prednisone, with rapid resolution of symptoms. One month after completion of prednisone, vision changes were again reported and she was restarted on a longer oral prednisone course. She then underwent definitive surgical management consisting of a total laparoscopic hysterectomy and bilateral salpingo-oophorectomy, with final pathology of benign endometrial hyperplasia. She has completed her steroid course without any symptoms. Given her complete pathologic response, she was subsequently placed into surveillance and is currently without evidence of disease. Prompt recognition and treatment of this rare immune-related adverse event led to the prevention of potential permanent, debilitating outcomes.